Learning geometry and values from patterns: Ethnomathematics on the batik patterns of Yogyakarta, Indonesia - Prahmana, Rully Charitas Indra; D'Ambrosio, Ubiratan (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2020)
In general, many people still view mathematics as a subject that is far from reality and culture in everyday life. Historically, in fact, mathematics is very close to daily life and was developed by humans in response to the surrounding phenomena. Indonesia has diverse cultures, including in Yogyakarta. This culture can be used to explore mathematical concepts as a transformational effort to bring mathematics closer to the reality and perception of its people. Besides, we can use culture as the basis of learning mathematics in schools. Therefore, this study seeks to explore a mathematical concept of geometry transformation in the Yogyakarta batik pattern. This is an ethnography study. The research data were collected through observations, literature studies, and interviews with the batik culture practitioner and artist to understand the batik techniques and moral, historical, and philosophical values in each batik motif. This study's results indicate that in Yogyakarta batik, it uses the concept of geometry transformation in the making of Yogyakarta's unique Batik motif. Besides that, each motif or pattern also contains local values. These, namely moral, historical, and philosophical values, can be felt, reflected, and applied in daily life, such as values that teach leadership, good deeds, and so on.